(untitled) (International Journal of Biology and Chemistry, 2023)
The process of reduction of Cu2+ from sulfuric acid solutions containing titanium dioxide as a dispersed phase (DP) was studied by electrolysis method. Composite electrochemical coatings (CEC) with a copper matrix with the inclusion of titanium dioxide were obtained. It has been established that with a change in the current density in the range of 50–300 A/m2, the content of titanium dioxide in the CEC noticeably decreases. It is shown that an increase in the concentration of DP in the range of 5-20 g/l and the concentration of sulfuric acid from 50 to 250 g/l leads to an increase in the content of titanium dioxide in the coatings. It was also found that with an increase in the stirring rate (100–600 rpm) and the concentration of Cu2+ (5–50 g/l), the content of titanium dioxide in the coating increases. It is noted that at low concentrations of Cu2+ in the electrolyte, a loose powdery precipitate formed, which is associated with the occurance of cathodic processes at current densities above the limiting current and with the co-release of hydrogen. The release of hydrogen bubbles additionally contributes to the loosening of the precipitate, and also prevents co-deposition of titanium dioxide. It is found that a dense uniform coating is obtained upon polarization by a cathode pulsed current. The proportion of inclusion of titanium dioxide in the composition of the composite coating with a change in current density in the range of 50-400 A/m2 reaches 2.1%. However, at current density above 400 A/m2, copper is deposited in the form of a powder, and no coating is formed. The obtained CEC were identified by electron scanning microscopy, and their elemental composition was determined, confirming the presence of titanium dioxide. The micrographs show a uniform distribution of TiO2 particles on the cathode surface.